AFKARUNA : Hamka's Doctoral Address At Al-Azhar : The Influence Of Muhammad Abduh In Indonesia - Kevin W. Fogg (Fakultas Agama Islam UMY, 2015)
This is a translation of the doctoral address given by Haji Abdul Malik Karim Amrullah (Hamka) when he received a doctorate honouris causa from al-Azhar University.